MODERASI BERAGAMA BERBASIS MA’HAD AL-JAMI’AH (STUDI DI UIN SUNAN AMPEL SURABAYA DAN IAIN SALATIGA) - Wasid; Abd Mujib Adnan (AL-FIKRAH: Jurnal Studi Ilmu Pendidikan dan Keislaman, 2024)
The issue of religious moderation on Islamic campuses, in particular, has evolved into a collective movement that must be nurtured to combat the spread of radicalism in higher education. The government has taken many measures so that colleges might play a role in protecting and saving students from extremism and terrorism movements, such as directions for establishing campus Islamic boarding schools (Ma'had al-Jami'ah). However, it is impossible to ignore the reality that these broad instructions leave a gap for different institutions to fill in building religious moderation for students so that each university has distinct qualities that the others do not. As a result, the focus of this research is on Ma'had al-Jami'ah at UIN Sunan Ampel Surabaya and IAIN Salatiga as research objects to identify a model for how Ma'had al-Jami'ah carries out the process of building religious moderation for students. This qualitative study was based on library sources and field surveys with Ma'had al-Jami'ah stakeholders. Aside from that, social capital theory served as a foundation for discovering each character to give rise to distinct methods of developing moderation in each Ma'had al-Jami'ah. The study results are as follows: First, the embryo of the existence of Ma'had al-Jami'ah at UIN Sunan Ampel Surabaya and IAIN Salatiga have similarities. Ma'had al-Jami'ah is an urgent need for universities for students to balance academic scientific traditions and spiritual traditions within the framework of al-Karima morals. Second, the social capital of Ma'had al-Jami'ah at UIN Sunan Ampel Surabaya and IAIN Salatiga in promoting religious moderation based on Ma'had al-Jami'ah is extensive and diverse. This diversity is so dynamic that it has given rise to a variety of activities that lead to students developing their religious moderation, and the three models for strengthening religious moderation at UIN Sunan Ampel Surabaya and IAIN Salatiga are all founded on Ma'had al-Jami'ah. As a result, the two universities' different social and cultural conditions give rise to various supporting activities for strengthening religious moderation. In general, the values of religious moderation are evident by placing al-Karima morals as one of the endings of all student activities.